Food, Body Function, and Leisure for Midlife Women: "If I Partake in That, I Will Suffer Consequences". (23rd November 2020) - Petty, Lisa; Engel, Joyce; Salfi, Jenn; Trussell, Dawn E.
Abstract: This study used hermeneutic phenomenology to explore the meaning that seven Canadian midlife women give to the experience of their changing bodies in relation to food, body function, and leisure. Findings emerge from in-depth, semi-structured research conversations and reveal these women have a contentious relationship with eating that arises from an awareness that what they choose to eat today will impact how they will feel tomorrow. The women in this study experience fatigue as a consequence of their food decisions, which then negatively impacts their leisure participation. The current study underscores the impact of food and body function not only on physical activity for midlife women but also on other leisure pursuits such as socializing with friends. These findings highlight the complex relationship between food, body function, and leisure in the context of daily life for these midlife women.